Å byggje ein minnestad. Falstadskogen 1945-2005 - Sem, Leiv (Tidsskrift for kulturforskning, 2005)
The article examines the development of a memorial at the site of the former WW2 prison camp SS-Strafgefangenenlager Falstad, one of the largest and most notorious camps in Norway. The memorial has undergone several significant changes in the PostWar years. Using Bakhtin’s concept of dialogue, the article examines how the memorial is built around a complex interaction between the components of the memorial, e.g. the landscape and various monuments, of which some are in concurrence, others in conflict. The memorial therefore has a rich repertoire of meaning which allows a number of interpretations. The article discusses how the memorial has been shaped and formed through negotiations between various concepts. By focussing on these dialogical aspects of the memorial, the author argues, one gains a deeper understanding of both the historical specificity of each component and the overall meaning.